The Influence of Learning Technology in Increasing Student Interest in Christian Religious Education Subjects at SDN Ciluar 3 - Uza Kristiyanto; Sri Rezeki (International Forum of Researchers and Lecturers, 2024)
Learning technology continues to develop as time goes by. Technology is the science of tools and skills that make humans work more efficiently. The implementation of daily learning often follows technological developments in the world of education, as do teachers and lecturers. In the field of education, technology has an influence on improving the quality of education, types of educational technology, information technology and communication and learning technology have a major role in learning. The role of technology in the field of education is as an information center and doing new things to illustrate learning and determine online learning methods. With increasingly developing technology, it can also provide benefits that have both good and bad impacts. One of the developments in technology has had a good influence by increasing self-openness in terms of expanding knowledge as information for all life in the world across borders, places and times. Negative impacts include changes in behavior, morals, rules or morals of life so that they conflict with the moral rules that apply in society. Therefore, to prevent the negative impact of using technology in learning, it is necessary to supervise parents and educators who work together in carrying out teaching and supervising children in using technology. The presence and function of technology in the world of education provides the development and growth of human resources as a determinant in achieving success in education. This kind of thing is caused by human resources themselves which are still lagging behind in using this technology in training. With today's technological developments in education, there are many new innovations to support learning. In this case, one way is to provide changes in educational facilities which are increasingly increasing and developing rapidly through technology.